Rapid Acidification of the Arctic Chukchi Sea Waters Driven by Anthropogenic Forcing and Biological Carbon Recycling. Issue 4 (21st February 2022) - Qi, Di; Wu, Yingxu; Chen, Liqi; Cai, Wei‐Jun; Ouyang, Zhangxian; Zhang, Yixing; Anderson, Leif G.; Feely, Richard A.; Zhuang, Yanpei; Lin, Hongmei; Lei, Ruibo; Bi, Haibo
Abstract: The acidification of coastal waters is distinguished from the open ocean because of much stronger synergistic effects between anthropogenic forcing and local biogeochemical processes. However, ocean acidification research is still rather limited in polar coastal oceans. Here, we present a 17‐year (2002–2019) observational data set in the Chukchi Sea to determine the long‐term changes in pH and aragonite saturation state (Ωarag ). We found that pH and Ωarag declined in different water masses with average rates of −0.0047 ± 0.0026 years −1 and −0.017 ± 0.009 years −1, respectively, and are ∼2–3 times faster than those solely due to increasing atmospheric CO2 . We attributed the rapid acidification to the increased dissolved inorganic carbon owing to a combination of ice melt‐induced increased atmospheric CO2 invasion and subsurface remineralization induced by a stronger surface biological production as a result of the increased inflow of the nutrient‐rich Pacific water. Plain Language Summary: Anthropogenic CO2 absorbed by the ocean leads to a lower pH and the calcium carbonate saturation state (Ω) and threatens the marine ecosystems state of healthiness via a process called ocean acidification (OA). The Arctic Ocean is particularly sensitive to OA because more CO2 can be dissolved in cold water. This study used the observations collected over 17 years from 2002 to 2019 to estimate long‐term trends of Ωarag and pH in the Chukchi Sea. The results show that rapid acidification occurred throughout all water masses from 2002 to 2019, leading to or approaching aragonite undersaturation. The rapid acidification is attributed to the enhanced increasing concentration of dissolved inorganic carbon. While sea ice melt induced uptake of anthropogenic CO2 partly explains the long‐term acidification, the remainder is due to the increased nutrient‐rich Pacific inflow water which promotes the high biological CO2 utilization in the surface waters but leads to stronger subsurface acidification due to the regenerated CO2 . We suggest that the acidity in Chukchi Arctic Shelf waters will increase in the future if the increased inflow of Pacific water continues. Key Points: pH and Ωarag declined at −0.0047 ± 0.0026 years −1 and −0.017 ± 0.009 years −1 from 2002 to 2019, 2–3 times greater than atmospheric CO2 projected The enhanced acidification in Chukchi Sea is mainly driven by enhanced dissolved inorganic carbon, owing to atmospheric CO2 uptake and biological activity Aragonite undersaturation in Pacific Winter Water has been observed from 2010; other water masses are expected to encounter Ωarag  < 1 within 15 years